The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1542/peds.2007-0978
|View full text |Cite
|
Sign up to set email alerts
|

Does Childhood Television Viewing Lead to Attention Problems in Adolescence? Results From a Prospective Longitudinal Study

Abstract: Childhood television viewing was associated with attention problems in adolescence, independent of early attention problems and other confounders. These results support the hypothesis that childhood television viewing may contribute to the development of attention problems and suggest that the effects may be long-lasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 24 publications
(30 reference statements)
11
102
0
4
Order By: Relevance
“…Ten articles mentioned an excessive exposure to television and/or video games and this is consistent with the scientific literature (Landhuis, Poulton, Welch, & Hancox, 2007; Weiss, Baer, Allan, Saran, & Schibuk, 2011; Zimmerman & Christakis, 2007). For example Le Monde (3 September 2014) reported: “Several scientifically sound studies have demonstrated that excessive exposure to screens [TV or video games] is linked to attention deficit.” Four articles highlighted the possible risk linked to the excessive consumption of certain food (sugar, colouring, additives), but another article, in agreement with short-term studies (Wolraich, Wilson, & White, 1995), stated that sugar is not a significant risk.…”
Section: Resultssupporting
confidence: 80%
“…Ten articles mentioned an excessive exposure to television and/or video games and this is consistent with the scientific literature (Landhuis, Poulton, Welch, & Hancox, 2007; Weiss, Baer, Allan, Saran, & Schibuk, 2011; Zimmerman & Christakis, 2007). For example Le Monde (3 September 2014) reported: “Several scientifically sound studies have demonstrated that excessive exposure to screens [TV or video games] is linked to attention deficit.” Four articles highlighted the possible risk linked to the excessive consumption of certain food (sugar, colouring, additives), but another article, in agreement with short-term studies (Wolraich, Wilson, & White, 1995), stated that sugar is not a significant risk.…”
Section: Resultssupporting
confidence: 80%
“…Some of these hypotheses attribute this effect to its violent content (Zimmerman & Christakis, 2007). Other hypotheses attribute this effect to the fast pace of entertainment media (i.e., the frequent use of cuts, edits, and fast character movement; Christakis, 2009;Christakis, Zimmerman, DiGiuseppe, & McCarty, 2004;Geist & Gibson, 2000;Halpern, 1975;Jensen et al, 1997;Landhuis, Poulton, Welch, & Hancox, 2007;Levine & Waite, 2000) or to the overall amount of time children spent consuming media (Christakis, 2009;Zimmerman & Christakis, 2007). Therefore, in this meta-analysis, we included all studies investigating the effect of either violent, fastpaced, or overall screen media use on ADHD-related behaviors.…”
Section: Media Contentmentioning
confidence: 99%
“…Often, authors intended to measure one of the ADHD-related behaviors (e.g., attention problems) but included a scale or items of a scale that also tapped other dimensions (e.g., Landhuis et al, 2007;Swing, Gentile, Anderson, & Walsh, 2010;Zimmerman & Christakis, 2007). Consequently, such a measure does not solely reflect the intended behavior.…”
Section: Coding Of Studiesmentioning
confidence: 99%
“…1 Exposure to television (TV) and videos before 3 years of age is associated with later problems with language development, [2][3][4] cognition, 5 attention, 6,7 executive functioning, 8 and school achievement. 9 These effects may be more pronounced in lowincome populations, where high media exposure is more prevalent.…”
mentioning
confidence: 99%